Influence of transformational leadership on innovative work behaviour, and mediating role of teachers self efficacy and innovative climate: insight from engineering institutions. (31st May 2019) - Khan, Sajid; Imran, Asma; Nafees, Muhammad
The aim of this research is to examine the influence of transformational leadership (TL) on innovative work behaviour (IWB) and mediating effect of teacher's self-efficacy (TSE) and innovative climate (IC). A quantitative research paradigm was employed using a questionnaire survey method; the data was collected from 112 academicians of engineering schools in the universities. Data has been analysed through Pearson correlation and linear regression tests. Results revealed that a positive relationship between transformational leadership and innovative work behaviour. The ordinary least square (OLS) method results supported the relationship between transformational leadership and innovative work behaviour via one mediating variable teachers self efficacy, but innovative climate does not mediates the relationship between transformational leadership and innovative work behaviour. The study contributes to the current knowledge regarding transformational leadership (TL) on innovative work behaviour (IWB) and mediating effect of teachers self efficacy (TSE) and innovative climate (IC).